Collective Female Identities in Discussions about Pussy Riot’s Performance - Agaltsova, Anna (Religion & gender, 2014)
In this paper, I address the issue of collective female identities in contemporary Russia. The Pussy Riot performance is regarded as a critical event that serves as a trigger for certain ‘groupness’. Taking critical event perspectives avoids framing the respondents with the researcher’s predetermined categories. The empirical data is collected via collective interviews with the diverse group of Moscovites. Analysis highlights the domination of an authoritarian/collectivistic interpretative repertoire in older participants’ discussions about the performance, which has resulted in the articulation of the image of the disadvantaged female and the denial of women’s agency. The younger participants, being familiar with a co-existing liberal interpretative repertoire, have continued to use a conservative repertoire to discuss Pussy Riot. This and a general lack of gender problematisation in the interviews indicate that feminist discourse is not at all widespread in the Moscovites’ everyday discourse.